"Pastorelle gentili" e "pescatrici leggiadre". Una favola pescatoria tra terra e mare: La Creazione della Perla di Gasparo Murtola - Myriam Chiarla (Annali Online dell'Università di Ferrara. Sezione Lettere)
The article presents the complete transcription of the "piscatory fable" The Creation of the Pearl, written by Gasparo Murtola on the occasion of the marriage between Margherita di Savoia and Francesco Gonzaga (celebrated in 1608) and published in a book containing various “piscatory” poems printed in 1617. The essay, which follows the text of The Creation of the Pearl,aims to propose a rapid overview of the literary tradition of the “piscatory” theme and its relationship with the pastoral literature. It also tries to illustrate the main issues of this "piscatory fable" by Murtola, such as the opposition between “land” and “sea” and the praise of Margherita di Savoia, compared to a pearl.